Case Report: A rare case of tuberculous otitis media mimicking chronic suppurative otitis media — an ongoing challenge - Shu, Chengjie; You, Taixian; Huang, Mei; Xu, Minglong; Zhang, Jianyong; Peng, Zhangli (Frontiers in Medicine, 2025)
Ear tuberculosis, a rare form of extrapulmonary tuberculosis caused by Mycobacterium tuberculosis, predominantly affects the middle ear. The common symptoms of ear tuberculosis include otorrhea, hearing loss, and facial nerve paralysis, and if left untreated, it can lead to complete deafness. Diagnosing ear tuberculosis can be challenging, as its symptoms often overlap with those of otitis media, leading to potential misdiagnosis. Early diagnosis and appropriate treatment are essential for a favorable prognosis. Delayed diagnosis or inadequate treatment can result in severe complications, including irreversible hearing loss and chronic ear problems. Therefore, raising awareness among healthcare providers about the clinical features and diagnostic approach to ear tuberculosis is critical for improving patient outcomes. This study presents the case of a 28-year-old patient with tuberculous otitis media (TOM), presenting with otorrhea, hearing loss, and facial paralysis. Additionally, a comprehensive literature review of 492 records published over the past decade in PubMed and the Web of Science databases was conducted. Our study summarizes the clinical manifestations, diagnostic methods, and treatment strategies of 118 patients with ear tuberculosis, offering valuable insights to support early diagnosis and intervention, ultimately reducing the risk of adverse outcomes.